Does Blast Medium Affect Heterotopic Ossification in a Blast‐amputation Model?. Issue 8 (August 2015) - Jaffe, David E.; Yoo, David; Blevins, Jason; Gasbarro, Gregory; Hughes, Tyler; Paryavi, Ebrahim; Nguyen, Thao; Fourney, William L.; Pellegrini, Vincent D.
Abstract: Background: Heterotopic ossification (HO) develops after nearly 2/3 of traumatic blast amputations in the contemporary battlefield. This phenomenon has potentially devastating consequences for servicemen and women and its pathophysiology warrants further investigation using a previously developed animal blast model. Questions/purposes: We asked, what is the (1) severity (quantity) and (2) type (location) of HO bone formation after a hindlimb blast amputation with two distinct blast media. We hypothesized that a more "war‐relevant" blast medium could be a more accurate model and potentially intensify the development of HO. Methods: Using a Sprague‐Dawley rat model, the pathophysiology of ectopic bone formation in a traumatic hindlimb blast amputation was evaluated. Twenty‐four animals underwent blast amputations and closure based on a previously established experimental model. Half the amputations were subjected to blasted sand and the other 1/2 to blasted water. Serial orthogonal radiography was performed on each animal until euthanasia at 24 weeks to track the development of HO. Heterotopic bone severity and type were assessed by three independent graders at each time using a novel grading scale to assess quantity and quality of HO. Results: All animals had radiographic evidence of HO develop. No differences were observed in ectopic bone development between sand and water blasting regarding severity or type at any time. Animals that received water and sand blasting had moderate HO develop at 24 weeks (median, 2.0 and 2.5 weeks, respectively; range, 1‐3 weeks; difference of medians, 0.5; p = 0.67). At the time of euthanasia, 10 animals that were water blasted had Type 3 HO compared with 11 in the sand‐blasted group (p = 1.00). Conclusions: Our study showed a clear development of HO after hindlimb blast amputation in a Sprague‐Dawley rat model; however, no difference was observed in HO development based on the type of blast media. This suggests it is the blast mechanism that induces ectopic bone development, regardless of the blasted medium. The grading scale we developed for our animal‐model study provided a reliable means of assessing HO severity and type. Clinical Relevance: We anticipate that future investigations will elucidate similarities between service members' wartime extremity injuries and the animal model used in our study, and with focused future research this model may have beneficial therapeutic implications as the pathophysiology of HO development is further understood.